A dinâmica territorial do município de Anápolis (GO): antigos distritos, novos municípios - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This dissertation, entitled “The Territorial Dynamics of the Municipality of Anápolis (GO): Old districts, new municipalities” aims to understand the process of political emancipation of the districts of Anápolis (GO), as well as the intermunicipal articulations that still prevail in the networks transport, health and education. It is worth mentioning that it was from the Anapolino territory that seven municipalities in Goiás (Brazabrantes, Campo Limpo de Goiás, Damolândia, Goianápolis, Nerópolis, Nova Veneza and Ouro Verde de Goiás) emerged. However, accompanied by district emancipation, Anápolis (GO), which until the 1940s exercised hegemony over regional economic activities, saw its area of influence, especially over its former districts, reduced due to the creation of Goiânia and Brasília . It also witnessed the formation of transport and service provision networks to intensify with the state capital, especially after the consolidation of the Metropolitan Region of Goiânia (RMG). However, even reducing its area of influence before its old districts, Anápolis (GO) branched its power to other fractions of the Goiás territory, a fact evidenced when considering the new regional arrangements of IBGE, especially the Immediate Geographic Region. In this sense, to arrive at such considerations, methodological procedures were adopted, among them the bibliographic review on the formation of municipalities, the collection of secondary data from the city halls, the Brazilian Institute of Geography and Statistics (IBGE) and the Mauro Borges Institute (IMB), in addition to the material sources provided by the Museu Histórico Alderico Borges de Carvalho. Then, fieldwork was carried out in each municipality that was formed from the Anapolino territory, to organize the image bank and confirm or refute the data collected in the office.
The territorial dynamics of the municipality of Anápolis (GO): old districts, new municipalities
Keywords: Município; Distrito; Anápolis; Redes; Municipalit; District; Anápolis; Networks; CIENCIAS HUMANAS::GEOGRAFIA; GEOGRAFIA HUMANA::GEOGRAFIA URBANA